Kemandirian santri di era global: Meneladani konsep pendidikan Kiai As'ad Syamsul Arifin - Zahroh, Jamilatus; Fahmi, Muhammad (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The era of globalization brings complex challenges that require generations of students to develop independence holistically. This research aims to examine the concept of student independence from the educational perspective of Kiai As'ad Syamsul Arifin and its relevance in the midst of contemporary global dynamics. This study uses a qualitative research method of field approach with phenomenological design, this study critically analyzes various primary and secondary sources including interviews with several teachers and students at the Salafiyah Syafi'yah Sukorejo Islamic Boarding School, works by Kiai As'ad, Islamic boarding school documents, scientific articles, and references related to Islamic boarding school education. The findings of the study revealed that Kiai As'ad built the concept of student independence through three main pillars: character building, example of ulama (qudwah hasanah), and mastery of applied science. Values such as spiritual independence, life skills, and adaptability are important foundations in facing the changing times. The analysis shows that although this concept develops in the traditional context of pesantren, its basic principles remain relevant to modern challenges such as digital disruption and multiculturalism. This study concludes that the Kiai As'ad educational model offers an integrative framework that combines moral toughness with global competence, while maintaining Islamic identity. The implications of this study recommend strengthening the pesantren curriculum that combines traditional values with the development of 21st century skills such as digital literacy, entrepreneurship, and critical thinking, without eroding the basic character of Islamic Boarding School education. Abstrak Era globalisasi membawa tantangan kompleks yang menuntut generasi santri untuk mengembangkan kemandirian secara holistik. Penelitian ini bertujuan mengkaji konsep kemandirian santri dalam perspektif pendidikan Kiai As’ad Syamsul Arifin serta relevansinya di tengah dinamika global kontemporer. Menggunakan metode penelitian kualitatif pendekatan lapangan dengan desain fenomenologi, studi ini menganalisis secara kritis berbagai sumber primer dan sekunder meliputi wawancara kepada beberapa guru dan santri di Pesantren Salafiyah Syafi’yah Sukorejo, karya-karya Kiai As’ad, dokumen pesantren, artikel ilmiah, dan referensi terkait pendidikan pesantren. Temuan penelitian mengungkap bahwa Kiai As’ad membangun konsep kemandirian santri melalui tiga pilar utama: pendidikan akhlak (character building), keteladanan ulama (qudwah hasanah), dan penguasaan ilmu terapan. Nilai-nilai seperti kemandirian spiritual, kecakapan hidup (life skills), dan adaptabilitas menjadi fondasi penting dalam menghadapi perubahan zaman. Analisis menunjukkan bahwa meskipun konsep ini berkembang dalam konteks tradisional pesantren, prinsip-prinsip dasarnya tetap relevan dengan tantangan modern seperti disrupsi digital dan multikulturalisme. Penelitian ini menyimpulkan bahwa model pendidikan Kiai As’ad menawarkan kerangka integratif yang memadukan ketangguhan moral dengan kompetensi global, sekaligus menjaga identitas keislaman. Implikasi penelitian ini merekomendasikan penguatan kurikulum pesantren yang memadukan nilai-nilai tradisional dengan pengembangan keterampilan abad 21 seperti literasi digital, kewirausahaan, dan pemikiran kritis, tanpa mengikis karakter dasar pendidikan pesantren.